PENINGKATAN KESADARAN HUKUM TENTANG PEMENUHAN HAK DAN KEWAJIBAN PEKERJA DALAM UNDANG-UNDANG KETENAGAKERJAAN DI INDONESIA - Irnawati , Irnawati; Andry Irdyansah; Radiana Fitriati; Efi Widya Astutik (JURNAL PENGABDIAN MANDIRI, 2024)
The increase in legal awareness regarding the fulfillment of workers' rights and obligations for prospective workers serves as an initial foundation in understanding and obtaining their rights to achieve justice and welfare within the labor regulations in Indonesia. The rights and obligations of workers in Law Number 13 of 2003 concerning employment mention the rights of workers, the right to equal treatment, the right to receive wages, leave, and other aspects that need to be understood by prospective workers, so they can uphold protection and guarantees for labor; implementing national instruments regarding labor rights that have been ratified. With the increase in capacity regarding Law Number 13 of 2003 on Employment, there is an 85% improvement in understanding workers' rights and obligations based on the pre-test and post-test results. The research method uses an analytical observational approach with a cross-sectional design, which is then combined with the OKULASI method. (Observasi, Edukasi, dan Evaluasi). The research results indicate that many job seekers are still unaware of their rights and obligations as workers, thus there is a need for socialization regarding workers' rights and obligations, so that in the future they can address issues related to obtaining legal protection and achievingjustice